CHARACTERISTICS OF THE ARTISTIC-AESTHETIC HERITAGE IN THE SCULPTOR MAHMOUD AJAMI’S WORKS - Asst. Prof. Dr. Hazem Aboudi Karim (Journal Park Publishing, 2022)
The research coped with "the characteristics of the artistic heritage in the work of the sculptor Mahmoud Ajami". The research shows the characteristics and effects of the ancient Iraqi civilization. It included four chapters: The first chapter included a presentation of the research problem, which was determined by answering the following question: